P–027 Does air pollution impact on semen parameters? Findings from a real-life cross-sectional study in white-European infertile men. (6th August 2021) - Belladelli, F; Pozzi, E; Boeri, L; Fallara, G; Capogrosso, P; Cignoli, D; Candela, L; Schifano, N; Raffo, M; Colandrea, A; Montorsi, F; Salonia, A
Abstract: Study question: We aimed to investigate the association between air pollutants levels and semen parameters in a cohort of white-European men seeking medical attention for couple's infertility. Summary answer: We found that Pm10, Pm 2.5, and NO2 levels were negatively associated with sperm morphology. What is known already: Air pollutants levels have been monitored closely for environmental and research issues in industrialized countries. Study design, size, duration: Data from 156 infertile men consecutively assessed between 01/2019 and 12/2020 were analysed. Participants/materials, setting, methods: Semen analyses were based on 2010 WHO reference criteria. We analysed the annual average level of the main markers of air pollution (Pm10, Pm2.5, and NO2) between 2014–2018 (Legambiente, 2020, Annual dossier series on air quality in Italy) relative to patients' addresses of the last 5 years. Health-significant comorbidities were scored with the Charlson Comorbidity Index (CCI). Descriptive statistics and linear regression analyses were used to test the association between air pollutants and semen parameters. Main results and the role of chance: Overall, median (IQR) age and BMI were 37 (33–41) years and 25.1 (23.4–27.3) kg/m2, respectively. A CCI≥1 was found in 12 (7.7%) men, and 47 (30.1%) participants were smokers. As for sperm parameters, semen volume, sperm concentration, sperm progressive motility and normal sperm morphology were 3 (2–4) ml, 18 (5–45.5) x10 6 /ml, 32 (22–45)% and 2 (1–3)%, respectively. Pm10 was negatively associated with sperm morphology (ß: –0.580, p = 0.001). Furthermore, Pm10 was found to be an independent predictor for sperm morphology worsening (ß: –0.729, p = 0.006) (Fig.1A), after adjusting for age, BMI, CCI and smoking status. Similarly, Pm2.5 levels were negatively associated with sperm morphology (ß: –0.595, p = 0.009) (Fig.1B). After adjusting for the same variables, the association between Pm2 and sperm morphology remained significant (ß: –0.724, p = 0.015) (Fig.1C). NO2 levels were found to be associated with sperm morphology worsening after adjusting for age, BMI, CCI, and smoking status (ß: –0.471, p = 0.006). Limitations, reasons for caution: It is a retrospective analysis at a single, tertiary-referral academic centre, thus raising the possibility of selection biases. Moreover, markers of air pollutions divided by residence may not completely evaluated the single patient exposure. Wider implications of the findings: In this cross-sectional study we found that Pm10, Pm 2.5, and NO2 levels were negatively associated with sperm morphology, while they were not consistently associated with an increased risk of other abnormal sperm parameters in infertile men. Further studies are needed to characterize air pollution effects on sperm parameters. Trial registration number: Not applicable